Caderneta da criança: uma análise do seu contrato de comunicação - Souza, Daniela Gomes de (Brasil, 2024)
The Child Health Handbook, published by the Ministry of Health, is essential for monitoring child health and development in Brazil. The aim of this study was to analyse the communication contract of the booklet, focusing on the types of language used, the description of the communication contract, the discursive organization and the evaluation of the validation parameters, as well as highlighting their importance for the reception of the discourse. The study is characterized as bibliographical research and has a qualitative and descriptive analytical approach, based on Semiolinguistic Theory. It uses the 5th edition of Caderneta as the corpus of analysis. Two communication contracts were identified: one aimed at families and the other at health professionals, each requiring different approaches to the production and interpretation of discourse. The relationship between the Ministry of Health, families and professionals is based on trust and cooperation, but the effectiveness of the booklet can be compromised by technical requirements. The conclusion is that the communication of the booklet is not fully effective for all audiences. In order to make improvements, it is essential to invest in continuing education and training campaigns for health professionals, promoting the value of the booklet and improving guidance for families.